DUKUNGAN INDONESIA TERHADAP TIMOR LESTE DALAM UPAYA MENJADI ANGGOTA ASEAN - Seran, Danius Reinaldo; Damayanti, Christy; Haqqi, Halifa (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
East Timor is the only country in the Southeast Asia region that has not yet joined the regional organization of ASEAN. Application of becoming an ASEAN member has been conducted since 2011. Submission of applications made by Timor Leste must be passed by several requirements and problems to obtain status as a member in ASEAN. As a neighboring country with Indonesia, naturally Indonesia participated in the submission of Timor Leste as a member of ASEAN. Research under the title "Indonesia's support of East Timor in an effort to become a member of ASEAN", has a problem in how Indonesia's support of East Timor is becoming an ASEAN member. The purpose of this research is to analyse and understand Indonesia's support of East Timor in an effort to become an ASEAN member. This research uses documentation methods. The data source used is primary and secondary data. Data will be analyzed by qualitative method of descriptive. The foundation of the theory used is national interest theory and Regional security. Based on the results of the study, it was concluded that the Indonesian form of support from the national interest in Timor Leste in an effort to become an ASEAN member where the support is implemented in the form of basic cooperation and training, also to stabilize the regional security of both countries in several field include politics, economics, security and education. Support in these areas has the aim of each to achieve Indonesia's national interests towards East Timor. Keyword : Timor Leste’s Application, Indonesia support, national interest.